Characterizing spatial immune architecture in metastatic melanoma using high-dimensional multiplex imaging - Eliason, Joel; Krishnan, Santhoshi; Fukuda, Yasunari; Bustos, Matias A.; Winkowski, Dan; Cho, Sungnam; Basi, Akshay; Baird, Regan; Grimm, Elizabeth A.; Davies, Michael A.; Hoon, Dave S. B.; Rao, Arvind; et al. (Frontiers in Immunology, 2025)
IntroductionImmune checkpoint inhibitors (ICIs) have significantly improved survival for patients with metastatic melanoma, yet many experienceresistance due to immunosuppressive mechanisms within the tumor immune microenvironment (TIME). Understanding how the spatial architecture of immune and inflammatory components changes across disease stages may reveal novel prognostic biomarkers and therapeutic targets.MethodsWe performed high-dimensional spatial profiling of two melanoma tissue microarrays (TMAs), representing Stage III (n = 157) and Stage IV (n = 248) metastatic tumors. Using imaging mass cytometry (IMC) and multiplex immunofluorescence (mIF), we characterized the phenotypic, functional, and spatial properties of the TIME. Cellular neighborhoods were defined by inflammatory marker expression, and spatial interactions between immune and tumor cells were quantified using nearest-neighbor functions (G-cross). Associations with survival were assessed using Cox proportional hazards models with robust variance estimation.ResultsStage IV tumors exhibited a distinct immune landscape, with increased CD74- and MIF-enriched inflammatory neighborhoods and reduced iNOS-associated regions compared to Stage III. Cytotoxic T lymphocytes (CTLs) and tumor cells were more prevalent in Stage IV TIME, while B cells and NK cells were depleted. Spatial analysis revealed that CTL–Th cell, NK–T cell, and B–NK cell interactions were linked to improved survival, whereas macrophage aggregation and excessive B–Th cell clustering in inflammatory regions correlated with worse outcomes. Organ-specific analyses showed that CTL infiltration near tumor cells predicted survival in gastrointestinal metastases, while NK–T cell interactions were prognostic in lymph node and skin metastases.DiscussionOur results reveal stage-specific shifts in immune composition and spatial organization within the melanoma TIME. In advanced disease, immunosuppressive neighborhoods emerge alongside changes in immune cell localization, with spatial patterns of immune coordination—particularly involving CTLs, NK cells, and B cells—strongly predicting survival. These findings highlight spatial biomarkers that may refine patient stratification and guide combination immunotherapy strategies targeting the inflammatory architecture of the TIME.